Mathematics in the modern world a CHED general education curriculum compliant - Sirug, Winston S. (Mindshapers Co., Inc., 2023)
"Mathematics in the modern world is designed to give a background in mathematics and mathematics as a tool taught in all programs at the college level. The text's primary objective is to develop the student's understanding of Mathematics in the modern world and the procedures needed to succeed in all college programs offerings by the Commission on Higher Education.."--Preface.